Nutritional enrichment of fruit peel wastes using lipid accumulating Aurantiochytrium strain as feed for aquaculture in the North-East Region of India - Saikia, Diganta Kumar; Chikkaputtaiah, Channakeshavaiah; Velmurugan, Natarajan (Environmental technology, 2024)
Utilization of fruit peel wastes to grow thraustochytrids for nutritional enrichment of wastes will lower environmental and economic costs associated with feedstock specific for aquaculture industries. In this study, high-carbohydrate content agricultural wastes, such as orange, pineapple, banana, and mausambi fruit peels were enriched with essential fatty acids producing thraustochytrids Aurantiochytrium sp. ATCC276. Characterizations of fruit peels revealed the presence of high carbohydrate content (9-16%) and reducing sugars essential for the growth of thraustochytrids. Optimization for lipid production of Aurantiochytrium sp. ATCC276 was carried out using response surface methodology (RSM) in combination with different concentrations of fruit peels in solid-state fermentation (SSF) conditions. Fruit peels composed of SSF experiments were designed using a central composite design. Aurantiochytrium sp. ATCC276 cells efficiently utilized the sugar components of fruit peels for their growth and lipid accumulation. Different SSF composites made of fruit peels were significantly enriched with fatty acids of Aurantiochytrium sp. ATCC276 cells. Culturing Aurantiochytrium sp. ATCC276 cells with these waste materials demonstrated distinct responses towards lipid accumulation at different compositions. The optimized SSF composite consists of 9.91 g 100 mL −1 orange, 5 g 100 mL −1 mausambi, 4.12 g 100 mL −1 pineapple, and 8.01 g 100 mL −1 banana peels and was enriched with 8.37% of Aurantiochytrium sp. ATCC276-derived lipids. This study expands the benefits and bioprocessing potential of essential fatty acids producing Aurantiochytrium sp. ATCC276 along with fruit peel wastes which a frontier in circular bioeconomy and valorizing waste for usage.